HEMODIALYSIS THERAPY SUSTAINED LOW EFFICIENCY DAILY DIALISIS FOR CHRONIC KIDNEY DESEASE PATIENT IN INTENSIVE CARE UNIT - Andry Nicolas, Gede (E-Jurnal Medika Udayana; vol 2 no5(2013):e-jurnal medika udayana)
Kidney failure is a clinical condition characterized by an irreversible decline in kidney function, to a degree that requires the permanent renal replacement therapy, in the form of dialysis or kidney transplantation. Dialysis consists of two major categories such as dialysis / hemodialysis intermittent and continuous dialysis / continuous renal replacement therapy (CRRT). SLEDD is the latest technique of renal replacement therapy that uses conventional hemodialysis equipment, but the therapeutic results like continuous dialysis therapy / CRRT were appropriate used in patien with critical ill.
Keywords: Chronic kidney desease, hemodyalisis, intensive care unit